Respostas

2014-04-06T18:34:03-03:00
 3 - X           X+1            X
---------   =   --------     -   -------        ⇒    
   8                4              3


 3 - X           X-1             X             
---------   -    --------     +   -------       = 0 ⇒     
   8                4              3 

mmc(3,4,8) = 24

 3 - X           X-1            X                        [ 3 x (3 - X) ] - [ 6 x (X- 1)] + [ 8 x (X)]
---------   -   --------     +   -------   = 0     ⇒   ----------------------------------------------------------  = 0
   8                4              3                                                24


9 - 3X - 6X - 6 + 8X  = 0 
-3X - 6X + 8x  = -9 + 6   x (-1)
3X + 6X - 8X = 9 - 6
X  = 3


      


1 5 1